Nucleocytoplasmic transport blockage by SV40 peptide-modified gold nanoparticles induces cellular autophagy - Tsai TL (Dove Medical Press, 2012)
Tsung-Lin Tsai,1,5 Chia-Cheng Hou,1,5 Hao-Chen Wang,1,5 Zih-Syuan Yang,2 Chen-Sheng Yeh,4 Dar-Bin Shieh,2,3 Wu-Chou Su1,51Institute of Basic Medical Sciences, 2Institute of Oral Medicine and Department of Stomatology, 3Center for Micro/Nano Science and Technology, 4Department of Chemistry, National Cheng Kung University, Tainan, Taiwan; 5Department of Internal Medicine, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, TaiwanAbstract: Gold nanoparticles modified with the nuclear localization signal from simian virus 40 large T antigen (GNP-PEG/SV40) accumulate on the cytoplasmic side of the nuclear membrane in HeLa cells. Accumulation of GNP-PEG/SV40 around the nucleus blocks nucleocytoplasmic transport and prevents RNA export and nuclear shuttling of signaling proteins. This long-term blockage of nucleocytoplasmic transport results in cell death. This cell death is not caused by apoptosis or necrosis because caspases 3 and 9 are not activated, and the expression of annexin V/propidium iodide is not enhanced in HeLa cells after treatment. Using transmission electron microscopy, autophagosomes and autolysosomes were seen to appear after 72 hours of treatment with GNP-PEG/SV40. Increasing levels of enhanced green fluorescent protein-microtubule-associated protein 1 light chain 3 (EGFP-LC3)-positive punctate and LC3-II confirmed GNP-PEG/SV40-induced autophagy. In SiHa cells, treatment did not induce accumulation of GNP-PEG/SV40 around the nucleus and autophagy. Treating cells with wheat germ agglutinin, a nuclear pore complex inhibitor, induced autophagy in both HeLa and SiHa cells. GNP-PEG/SV40-induced autophagy plays a role in cell death, not survival, and virus-mediated small hairpin RNA silencing of Beclin-1 attenuates cell death. Taken together, the results indicate that long-term blockade of nucleocytoplasmic transport results in autophagic cell death.Keywords: gold nanoparticles, nucleocytoplasmic transport blockage, autophagy, wheat germ agglutinin